2006
DOI: 10.1073/pnas.0510171102
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the tumor suppressor gene TCF21 on 6q23-q24 in lung and head and neck cancer

Abstract: The identification of tumor suppressor genes has classically depended on their localization within recurrent regions of loss of heterozygosity. According to Knudson's two-hit hypothesis, the remaining allele is lost, either genetically or, more recently identified, through epigenetic events. To date, retrospective analyses have determined promoter methylation as a common alternative alteration in cancer cells to silence cancer-related genes. Here we report an application of restriction landmark genomic scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
136
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(158 citation statements)
references
References 41 publications
11
136
0
11
Order By: Relevance
“…TCF21 is a class II basic helix-loop-helix transcription factor, which is expressed in the mesenchyme of developing organs, including lung, kidney and epicardium (15). TCF21 binds specific DNA sequences and negatively regulates various cell differentiation through modulating cell cycle arrest and tissue-specific gene expression (15), indicating that TCF21 has a role in the development of malignant tumors (16). Expression quantitative trait locus (eQTL) data and a reporter gene assay showed that the C allele of rs12190287 increased the expression of TCF21 in vascular smooth muscle cells (VSMCs) (2,17).…”
Section: Discussionmentioning
confidence: 99%
“…TCF21 is a class II basic helix-loop-helix transcription factor, which is expressed in the mesenchyme of developing organs, including lung, kidney and epicardium (15). TCF21 binds specific DNA sequences and negatively regulates various cell differentiation through modulating cell cycle arrest and tissue-specific gene expression (15), indicating that TCF21 has a role in the development of malignant tumors (16). Expression quantitative trait locus (eQTL) data and a reporter gene assay showed that the C allele of rs12190287 increased the expression of TCF21 in vascular smooth muscle cells (VSMCs) (2,17).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant lesions are often defined by their differentiation status, where benign tumors and lowgrade cancers typically retain their epithelial phenotype and malignant cells acquire more fibroblastic mesenchymal phenotype (20). As mentioned in the results, Smith et al (11) previously reported highly significant induction of WNT4 expression in lung cancer cells (TCF21 expression negative) when transfected with TCF21. WNT4 has been associated previously with epithelialmesenchymal transition and epithelial phenotype (22).…”
Section: Discussionmentioning
confidence: 69%
“…Using restriction landmark genomic scanning, Smith et al (11) identified TCF21 as a candidate tumor suppressor at 6q23-q24 that is epigenetically inactivated in lung and head and neck cancers. In our article, using DNA sequencing, we examined lung cancer and bronchial epithelial cell lines for methylation of the CpG island within exon 1 of the TCF21 gene (GenBank accession no.…”
Section: Introductionmentioning
confidence: 99%
“…Among these 67 epigenetically induced or suppressed genes, some genes were previously reported to be related with lung cancer. TCF21, which regulates the mesenchymal cell transition into epithelial cells, has been demonstrated previously to be silenced in most head and neck squamous cell carcinomas and non-small-cell lung cancer tumor cells (Smith et al, 2006). SOSTDC1 has been reported previously to regulate the Wnt receptor signaling pathway, while Wnt has been implicated in skin cancer, lung cancer, bladder cancer, and leukemia, and may be oncogenic in other cancers (Reya and Clevers, 2005;Barker and Clevers, 2006;Polakis, 2007).…”
Section: Discussionmentioning
confidence: 99%